Development of a novel assay for IGFBP-2 complexed with IGF-I and-II in human serum. (April 2020) - Agerholm, Jonas; Hjortebjerg, Rikke; Espelund, Ulrick; Rasmussen, Torben Riis; Folkersen, Birgitte; Bjerre, Mette; Frystyk, Jan
Abstract: Background: Insulin-like growth factor binding-protein 2 (IGFBP-2) was originally identified as an IGF-carrier, governing IGF half-life, tissue accessibility and biological effects. Later, IGFBP-2 was discovered to possess IGF-independent effects. IGFBP-2 circulates in several forms, as free protein, complexed with IGF-I or IGF-II, or as IGFBP-2 fragments. The various IGFBP-2 forms are all included when measuring serum IGFBP-2 concentrations by immunoassay (i.e., immunoreactive (ir-)IGFBP-2). In this study, we describe a novel method to measure the amount of IGF that circulates bound to IGFBP-2. Method: IGFBP-2 was immunoprecipitated from human serum using magnetic beads, which were subsequently eluted by acidification. After neutralization, eluates were assayed for ir-IGFBP-2, IGF-I and IGF-II and compared to serum concentrations. This allowed measurement of IGFBP-2-compexed IGF-I and IGF-II, respectively. To test the method clinically, serum from 146 patients with lung cancer, 151 patients with non-cancer pulmonary diseases and 28 healthy controls were analyzed. Results: We immuno-precipitated 97 ± 3.3% of serum IGFBP-2 and recovered > 75% of IGFBP-2-complexed IGFs, with intra- and inter-assay coefficient of variations (CVs) averaging < 5% and < 13%, respectively. No co-precipitation with IGFBP-1, −3 or − 4 was detected. Serum levels of ir-IGFBP-2 (median [25;75%]) differed between groups (cancer patients vs. non-cancer patients vs. healthy controls): 342 [260;480] vs. 262 [189;388] vs. 190 [141;269] μg/l ( p  < .0001). In parallel with this, concentrations of IGF-II carried by IGFBP-2 averaged: 45.0 [33.3;52.5] vs. 34.2 [25.4;46.1] vs. 19.8 [14.1;26.0] μg/l ( p  < .0001), and concentrations of IGF-I 8.0 [5.2;11.8] vs. 5.4 [3.6;7.3] vs. 7.0 [3.8;13.0] μg/l ( p  < .0001). Thus, IGFBP-2 carried more IGF-II than IGF-I in all groups (p < .0001). When expressed relative to IGF-concentrations, IGFBP-2 carried 9.0 [5.3;15.5] % of the IGF-I and 4.8 [2.9;5.8] % of the IGF-II in serum from healthy subjects. Notably, in patients, IGFBP-2 carried relatively less IGF-I, but more IGF-II ( p  < .0001). Conclusion: Using our novel assay, we demonstrate: that IGFBP-2 carries ≈10% of circulating IGF-I and ≈5% of circulating IGF-II in healthy subjects; that IGF-II is the primary ligand for IGFBP-2; and that IGFBP-2 carries even more IGF-II in patients than in healthy subjects. Thus, our assay may provide information on IGFBP-2 beyond what is achievable by simply measuring ir-IGFBP-2. Highlights: IGFBP-2 levels are elevated in lung cancer and are associated with poor prognosis. IGFBP-2 circulates both in complexes with IGF-I or IGF-II and as free protein. We developed a novel assay to measure IGFBP-2 complexed with IGF-I and IGF-II, respectively. We tested this novel method in patients with lung cancer, other lung diseases and healthy people. >50% of IGFBP-2 in serum carries IGF. IGF-II is the primary ligand, and IGFBP-2 carries even more IGF-II in patients than healthy people.